PENGARUH BUDAYA PASIEN TERHADAP PEMAHAMAN PENYAKIT DAN PENGOBATAN: IMPLIKASI HUKUM KESEHATAN RUMAH SAKIT DALAM MENGAKOMODASI PERBEDAAN BUDAYA UNTUK PENINGKATAN PELAYANAN - Hotmaria Hertawaty Sijabat; Gunawan Widjaja (CV. ADIBA AISHA AMIRA, 2025)
This study aims to examine the influence of patient culture on their understanding of disease and treatment, as well as the implications of hospital health law in accommodating cultural differences to improve the quality of health services. Patient culture includes beliefs, values, language, and traditional practices that significantly shape perceptions and responses to treatment received. This study uses a literature review method with a descriptive-analytical approach to health law, patient culture, and hospital service literature. The results show that a lack of cultural sensitivity in healthcare services has the potential to cause misunderstandings, treatment refusal, and the risk of treatment failure, while also increasing the risk of legal litigation for hospitals. Therefore, hospitals are required to apply the principle of non-discrimination, provide easily understandable information, and develop cultural competence policies and training for medical personnel. Clear legal implications and integrative cultural-legal strategic steps are key to creating inclusive, dignified, and effective healthcare services. This study provides conceptual and practical contributions to the development of culturally responsive healthcare systems in Indonesia and other multicultural countries.